Ghostgirl : Homecoming - Hurley, Tonya (New York : Little, Brown and Co., 2009)
When Petula becomes deathly ill, her sister Scarlet seeks help from former classmate Charlotte, for whom the afterlife has become burdensome, leaving her just as insecure and isolated as she was while she was alive.
012-up.
Accelerated Reader AR
Keywords: Future life -- Juvenile fiction; Sisters -- Juvenile fiction; Coma -- Juvenile fiction; Death -- Juvenile fiction; Friendship -- Juvenile fiction